2022
DOI: 10.1002/adma.202110305
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Physicochemical Properties of Antibody–Nanoparticle Conjugates for Improved Tumor Targeting

Abstract: Tumor‐targeted antibody (mAb)/fragment‐conjugated nanoparticles (NPs) represent an innovative strategy for improving the local delivery of small molecules. However, the physicochemical properties of full mAb–NPs and fragment–NPs—that is, NP material, size, charge, as well as the targeting antibody moiety, and the linker conjugation strategies—remain to be optimized to achieve an efficient tumor targeting. A meta‐analysis of 161 peer‐reviewed studies is presented, which describes the use of tumor‐targeted mAb–N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 120 publications
3
33
0
Order By: Relevance
“…The inability of the AuNP to successfully embed completely within the gel-phase bilayer (i.e., interfacial interaction) has potential implications for other hard–soft matter or lipid–NP interactions and other biological–bilayer interactions, as other materials with similar properties may exhibit similar behavior. The ability of the AuNP to localize within the central core of the fluid-phase bilayer has potential applications in targeting specific membrane embedded protein anchorage motifs (i.e., nonpolar/hydrophobic regions of proteins). , Specificity of these domains and functionality can be further enhanced via AuNP–protein/peptide conjugation, while cell penetration can be enhanced via alteration of ligand coating and conjugation to cell-penetrating peptides . The ability of the AuNP to potentially translocate across the gel-phase bilayer upper leaflet surface allows it to potentially illicit effects and/or delivery compounds to the cell without direct interference with intracellular organelles or other cellular constituents.…”
Section: Resultsmentioning
confidence: 99%
“…The inability of the AuNP to successfully embed completely within the gel-phase bilayer (i.e., interfacial interaction) has potential implications for other hard–soft matter or lipid–NP interactions and other biological–bilayer interactions, as other materials with similar properties may exhibit similar behavior. The ability of the AuNP to localize within the central core of the fluid-phase bilayer has potential applications in targeting specific membrane embedded protein anchorage motifs (i.e., nonpolar/hydrophobic regions of proteins). , Specificity of these domains and functionality can be further enhanced via AuNP–protein/peptide conjugation, while cell penetration can be enhanced via alteration of ligand coating and conjugation to cell-penetrating peptides . The ability of the AuNP to potentially translocate across the gel-phase bilayer upper leaflet surface allows it to potentially illicit effects and/or delivery compounds to the cell without direct interference with intracellular organelles or other cellular constituents.…”
Section: Resultsmentioning
confidence: 99%
“…[ 454 ] Additionally, Mittelheisser et al further confirmed that the tumor‐targeting antibody‐nanoparticle conjugates could exhibit significantly increased tumor uptake compared with non‐targetable nanoparticles in a recent meta‐analysis study. [ 655 ] Also, as mentioned before, various studies have demonstrated the enhanced tumor accumulation of antibody‐conjugated nanoparticles in comparison with that of non‐targetable nanoparticles in both in vitro cell models and in vivo mouse models. Besides, compared with non‐targetable nanoparticles, the antibody‐modified nanoparticles can realize enhanced anticancer efficacy since the antibody functionalization can promote the cellular uptake of the nanoparticles via the receptor‐mediated endocytic pathway.…”
Section: Discussionmentioning
confidence: 92%
“…The acryl function enabled to covalently bind the complexes to the host matrix thanks to its involvement in the copolymerization process and to avoid a possible leakage from the particles over time. At the same period, [Eu (48) 3 ] doped PSt NPs were also commercialized and have been extensively used by Härmä and colleagues over the years for improving bioanalytical methods (immunoassays, [136][137][138][139] cell imaging, 140 protein quantification 141 and protein aggregation 142,143 ). The 107 nm NPs in particular were found to contain 31000 chelates and to exhibit an Eu-based luminescence emission lifetime of circa 720 µs.…”
Section: Polymer Npsmentioning
confidence: 99%
“…multiple analysis with a same sample 44 or multimodal analytical devices. 45 On the other hand, the larger size and composition of NPs compared to Ln complexes can bring significant issues regarding toxicity, 46,47 possible unwanted size dependent pharmacokinetic and bio-distribution properties, 48 or simple stability troubles such as leaching in biological media. 49,50…”
Section: Basic Spectral Properties Of Ln Ion In Complexes and Their C...mentioning
confidence: 99%
See 1 more Smart Citation